1992
DOI: 10.1104/pp.100.3.1092
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry of Spinach Chloroplasts

Abstract: Intact spinach (Spinacia oleracea) chloroplasts, thylakoid membranes, and inside-out or right-side-out thylakoid vesicles have been characterized by flow cytometry with respect to forward angle light scatter, right angle light scatter, and chlorophyll fluorescence. Analysis of intact chloroplasts with respect to forward light scatter and the chlorophyll fluorescence parameter revealed the presence of truly "intact" and "disrupted" chloroplasts. The forward light scatter parameter, normally considered to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…These findings regarding vacuole characterization by microscopy and flow cytometry analysis were previously summarized in the book chapter by Papadakis et al [ 5 ]. So far, only spinach chloroplasts [ 11 ] and rice protoplasts [ 12 ] have been studied by flow cytometry. The present results open new perspectives for future work concerning the study of calcium transport across the tonoplast with calcium sensitive fluorescent probes and flow cytometry analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These findings regarding vacuole characterization by microscopy and flow cytometry analysis were previously summarized in the book chapter by Papadakis et al [ 5 ]. So far, only spinach chloroplasts [ 11 ] and rice protoplasts [ 12 ] have been studied by flow cytometry. The present results open new perspectives for future work concerning the study of calcium transport across the tonoplast with calcium sensitive fluorescent probes and flow cytometry analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thylakoid membranes from several plants have been demonstrated to possess lectins and, in at least one case, they have been shown to interact with Rubisco in a galacturonic acid-dependent manner (Schröder and Petit 1992, Hincha et al 1993, Aleksidze et al 2002. More recently, it was shown that some lectins in stroma provide ligands to Rubisco (Kovalchuk et al 2012).…”
Section: The Role Of Lectins In Plantsmentioning
confidence: 99%
“…ISAC member Bob Ashcroft did some of the first work (81) in the flow analysis of chloroplasts and was able to characterize intact chloroplasts and thylakoids prepared from spinach and maize by using forward and 90°light scatter and fluorescence emission signals. ISAC member Patrice Petit took this work forward by using forward angle and 90°light scatter and chlorophyll autofluorescence measurements to characterize the integrity of isolated spinach chloroplasts and, in combination with labeling with fluorescein isothiocyanate-linked lectins, to distinguish intact chloroplasts from thylakoid membranes and from various chloroplast membrane subfractions (82). ISAC member Julie Auger was involved in the further characterization of the fluorescence signals produced by chloroplasts (83).…”
Section: Flow Analysis and Sorting Of Organellesmentioning
confidence: 99%